Clinical assessment form - Md Mustafa, Md Muziman Syah; Ahmad, Norsham; Yusof, Firdaus (2020)
The clinical assessment form is developed as a tool to evaluate clinical performance of Optometry students in examining and managing their attended patients/cases in Primary Optometry Clinic I, II and III. It provides an assessment rubric to assist a clinical supervisor in categorising the students as a competent or incompetent with 10 grading scales for every attended case.